2015
DOI: 10.1097/iop.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Pregabalin for Attenuation of Postoperative Pain After Eyelid Surgery

Abstract: Pregabalin is effective in reducing postoperative pain after oculoplastic procedures when compared with placebo. It may be a useful adjunct for pain control in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…The major advantages of PGB include its relative reliability, ease of use, and high tolerability [ 26 ]. Thus far, it has been used for NeP associated with alterations in both the central nervous system (e.g., spinal cord injury) [ 23 ] and peripheral nervous system (postoperative pain) [ 27 32 ], and the current study proved that it is also effective in alleviating neuropathic leg pain and improving ADL/QOL, including sleep quality, in LSS patients. These findings indicate that persistent leg pain in LSS patients that is refractory to NSAIDs can be effectively controlled using PGB, which is initiated with a low dose that is gradually increased.…”
Section: Discussionmentioning
confidence: 53%
“…The major advantages of PGB include its relative reliability, ease of use, and high tolerability [ 26 ]. Thus far, it has been used for NeP associated with alterations in both the central nervous system (e.g., spinal cord injury) [ 23 ] and peripheral nervous system (postoperative pain) [ 27 32 ], and the current study proved that it is also effective in alleviating neuropathic leg pain and improving ADL/QOL, including sleep quality, in LSS patients. These findings indicate that persistent leg pain in LSS patients that is refractory to NSAIDs can be effectively controlled using PGB, which is initiated with a low dose that is gradually increased.…”
Section: Discussionmentioning
confidence: 53%
“…Thirty-one studies had included data on nausea prevalence after pregabalin administration, 13 , 21 , 24 , 26 , 28 , 30 , 33 , 37 , 44 , 46 , 47 , 50 52 , 54 , 56 , 57 , 59 , 60 , 63 65 , 67 , 68 , 70 , 71 , 77 , 85 , 86 , 88 with a total of 1067 patients taking pregabalin and 1038 patients on the control treatment. It was found that there was no difference in nausea incidence in cardiothoracic surgery, ENT surgery, gynecologic surgery, laparoscopic cholecystectomy, and spine surgery between pregabalin and control treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact mechanism through which GBT, by involving multiple players, exerts its analgesic effect is complex and not definitively clarified ( Taylor and Harris, 2020 ). In ocular neuropathies, systemic administration of GBT or its analog pregabalin has been demonstrated to reduce pain ( Lichtinger et al, 2011 ; Pakravan et al, 2012 ; Wei et al, 2015 ; Ongun and Ongun, 2019 ; Yoon et al, 2020 ), although its efficacy in counteracting ocular pain in patients with DED has been questioned ( Ozmen, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic drugs include gabapentin (GBT), a structural analog of gamma-amino butyric acid that has been introduced as an adjunctive therapy in epilepsy and is presently widely used to treat several kinds of neuropathic pain. The possibility that GBT may counteract ocular pain has been suggested by several studies ( Lichtinger et al, 2011 ; Pakravan et al, 2012 ; Wei et al, 2015 ; Ongun and Ongun, 2019 ; Yoon et al, 2020 ), since the first demonstration of systemic GBT efficacy in providing significant pain relief in glaucomatous patients ( Kavalieratos and Dimou, 2008 ). At least some of the clinical effects of GBT are due to high affinity interactions with the α2δ1 auxiliary subunit of presynaptic voltage-gated calcium channels ( Taylor and Harris, 2020 ).…”
Section: Introductionmentioning
confidence: 99%